The Accuracy of Smartphone Sound Level Meter Applications (SLMAs) in Measuring Sound Levels in Clinical Rooms - Serpanos, Yula C.; Schoepflin, Janet R.; Cox, Steven R.; Davis, Diane (Journal of the American Academy of Audiology, 2021)
Background The accuracy of smartphone sound level meter applications (SLMAs) has been investigated with varied results, based on differences in platform, device, app, available features, test stimuli, and methodology.Purpose This article determines the accuracy of smartphone SLMAs with and without calibration of external and internal microphones for measuring sound levels in clinical rooms.Research Design Quasi-experimental research design comparing the accuracy of two smartphone SLMAs with and without calibration of external and internal microphones.Data Collection and Analysis Two iOS-based smartphone SLMAs (NIOSH SLM and SPL Meter) on an iPhone 6S were used with and without calibrated external and internal microphones. Measures included: (1) white noise (WN) stimuli from 20 to 100 dB sound pressure level in a sound-treated test booth and (2) sound levels in quiet in four nonsound-treated clinical rooms and in simulated background sound conditions using music at 45, 55, and 80 dBA. Chi-square analysis was used to determine a significant difference (p ≤ 0.05) in sound measures between the SLMAs and a Type 1 SLM.Results Measures of WN signals and room sound level measures in quiet and simulated background sound conditions were significantly more accurate at levels ≥ 40 dBA using the SLMAs with calibrated external and internal microphones. However, SLMA measures with and without calibration of external and internal microphones overestimated sound levels < 40 dBA.Conclusion The SLMAs studied with calibrated external or internal microphones are able to verify the room environment for audiologic screening at 1,000, 2,000, and 4,000 Hz at 20 dB hearing level (American Academy of Audiology and American Speech-Language-Hearing Association) using supra-aural earphones (American National Standards Institute S3.1–1999 [R2018]). However, the tested SLMAs overestimated low-level sound < 40 dBA, even when the external or internal microphones were calibrated. Clinicians are advised to calibrate the microphones prior to using measurement systems involving smartphones and SLMAs to measure room sound levels and to monitor background noise levels throughout the provision of clinical services.
Keywords: sound levels; calibration; smartphone; sound level meter; sound level meter applications